2012
DOI: 10.1007/s00431-012-1858-6
|View full text |Cite
|
Sign up to set email alerts
|

Grisel syndrome as a complication of Kawasaki disease: a case report and review of the literature

Abstract: Pediatricians should be aware of Grisel syndrome as a possible complication of Kawasaki disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…10,11 Kawasaki disease is a very frequent acute febrile vasculitis of childhood that has also been related to Grisel syndrome. 12 After the introduction of monopolar suction electrocautery in adenoidectomy, an increased incidence of Grisel syndrome has been observed when compared with bipolar coagulation for bleeding control. 13 Karkos et al conducted a systematic review of 71 articles, which included 96 patients with C1-C2 subluxation with no history of previous trauma.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Kawasaki disease is a very frequent acute febrile vasculitis of childhood that has also been related to Grisel syndrome. 12 After the introduction of monopolar suction electrocautery in adenoidectomy, an increased incidence of Grisel syndrome has been observed when compared with bipolar coagulation for bleeding control. 13 Karkos et al conducted a systematic review of 71 articles, which included 96 patients with C1-C2 subluxation with no history of previous trauma.…”
Section: Discussionmentioning
confidence: 99%
“…8 The syndrome can be caused by various infectious agents, including Streptococcus pyogenes, Bacteroides ureolyticus, 9 Mycobacterium tuberculosis, 10 Pseudomonas aeruginosa, Staphylococcus aureus, methicillin-resistant Staphylococcus epidermidis, the Epstein-Barr virus, and Kawasaki disease. 11,12 In our case study, it was concluded that Grisel's syndrome developed secondary to the patient's recent upper respiratory tract viral infection.…”
Section: Discussionmentioning
confidence: 69%
“…Non‐traumatic atlantoaxial subluxation, known as Grisel syndrome, is an uncommon complication of upper neck inflammation and head and neck surgery 2 . The first report of KD associated with cervical subluxation, in a patient from Japan, was published recently 3 . The Japanese case was published after our search of Medline, EMBASE and PubMed with the search strategy Kawasaki disease AND subluxation in March 2012.…”
Section: Discussionmentioning
confidence: 99%
“…If the subluxation is longstanding, surgical fusion may be required. If left untreated, sequelae can range from mild paraesthesias to quadriplegia to acute respiratory failure 3 . However, when promptly and effectively treated, the prognosis is excellent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation